Volume 4: 24th Design for Manufacturing and the Life Cycle Conference; 13th International Conference on Micro- And Nanosystems 2019
DOI: 10.1115/detc2019-97231
|View full text |Cite
|
Sign up to set email alerts
|

Design Principle Cards: Toolset to Support Innovations With Additive Manufacturing

Abstract: Additive manufacturing (AM) continues to play an important role in product development, and many companies are searching for how to best integrate AM into their products, business models, and design processes. Often, AM is integrated into later stages of the design process for products during manufacturing and production. However, there is an opportunity to introduce AM in early-stage design, which could spark new business models and services in addition to re-thinking manufacturing for products. The central r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Blösch-Paidosh & Shea, 2019;Lindwall & Törlind, 2018, and design principles, e.g. ;Perez et al, 2019;Lauff et al, 2019), but more research is needed on how to fully include these in industrial design practices.…”
Section: Discussionmentioning
confidence: 99%
“…Blösch-Paidosh & Shea, 2019;Lindwall & Törlind, 2018, and design principles, e.g. ;Perez et al, 2019;Lauff et al, 2019), but more research is needed on how to fully include these in industrial design practices.…”
Section: Discussionmentioning
confidence: 99%
“…They are derived from a large pool of experience or empirically, e.g. (Lauff et al, 2019;Valjak and Bojčetić, 2019).  AM guidelines provide context-dependent statements that are empirically tested or based on extensive experience and are more restrictive and less general than principles, e.g.…”
Section: Methodsmentioning
confidence: 99%
“… AM guidelines provide context-dependent statements that are empirically tested or based on extensive experience and are more restrictive and less general than principles, e.g. (Lauff et al, 2019;Valjak and Bojčetić, 2019).  AM rules are reliable statements derived from quantitative studies that relate to the expression of features (wall thickness, radii, etc.…”
Section: Methodsmentioning
confidence: 99%
“…The crowdsourced DP developed by Perez et al were later expanded and reformulated to support innovation with AM during early design stages and are formalised in the form of 27 AM Principle Cards (Lauff et al, 2019;Perez, Hilburn, et al, 2019). Here the AM design knowledge is written with formal syntax and further described with schematics and examples.…”
Section: Figure 1 Flow Diagram Of Conducted Systematic Literature Reviewmentioning
confidence: 99%
“…compare all studies found on DH in the context of AM regarding the definition of DH provided in the study, the number of DH given, and the design phase where the DH are indented to be applied. (Lauff et al, 2019;Perez, Hilburn, et al, 2019). Here the AM design knowledge is written with formal syntax and further described with schematics and examples.…”
Section: Figure 1 Flow Diagram Of Conducted Systematic Literature Reviewmentioning
confidence: 99%